Step-by-step explanation:
2x = y-10
Rewrite as: 2x + 10 = y
Therefore:
2x+10 = y
2x +7 = 2y
Subtract the equations:
2x + 10 = y
- 2x + 7 = 2y
______________
3 = -y
Therefore y = -3
Substiture y = -3 into the second equation:
2x + 7 = 2(-3)
2x + 7 = -6
2x = -13
x= -6.5
Answer : (-6.5, -3)
24 because when you plug in 0 for both x and y:
0=12(0)+24
12*0=0, leaving you with 24.
Answer:
3/1
Step-by-step explanation:
Answer:
The third one ![\sqrt[3]{15}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B15%7D)
Step-by-step explanation:
<span>8-5x=8+2x is to be solved for x.
Group the x terms together: </span><span>8=8+2x+5x => 0 = 7x => x = 0</span>